Pharmacokinetics of 18F-labeled fleroxacin in rabbits with Escherichia coli infections, studied with positron emission tomography. - Fischman, A J (1992)
18F-labeled fleroxacin was used to measure the pharmacokinetics of fleroxacin in healthy and infected animals by positron emission tomography (PET) and tissue radioactivity measurements. In all experiments, a pharmacological dose of unlabeled drug (10 mg/kg) was coinjected with the tracer. The pharmacokinetics of [18F]fleroxacin was measured in groups of healthy mice (n = six per group) at 10, 30, 60, and 120 min after injection and in groups of rats with Escherichia coli thigh infections (n = six per group) at 60 and 120 min after injection by radioactivity measurements in excised tissues. In healthy rabbits (n = 4) and in rabbits with E. coli thigh infections (n = 4), tissue concentrations of drug were determined by serial PET imaging over 2 h; after the final image was acquired, animals were sacrificed and concentrations measured by PET were compared with the results of tissue radioactivity measurements. In all three species, there was rapid equilibration of [18F]fleroxacin to significant concentrations in most peripheral organs; low concentrations of drug were detected in the brain. Accumulations of radiolabeled drug in infected and healthy thigh muscles were similar. Peak concentrations of drug of more than three times the MIC for 90% of members of the family Enterobacteriaceae (greater than 100-fold for most organisms) were achieved in all tissues except brain and remained above this level for more than 2 h. Especially high peak concentrations were achieved in the kidney (greater than 75 micrograms/g), liver (greater than 50 micrograms/g), blood (greater than 25 micrograms/g), and bone and lung (greater than 10 micrograms/g).Since the MICs for 90% of all Enterobacteriaceae are <2 micrograms/ml, fleroxacin should be particularly useful in treating gram-negative infections affecting these tissues. In contrast, the low concentration of drug delivered to the brain should limit the toxicity of the drug for the central nervous system.